Одностороння відмова від договору сурогатного материнства - Коренга, Ю.; Korenga, Yu. (Східноєвропейський національний університет імені Лесі Українки, 2013)
У статті вивчено доктринальне осмислення інституту односторонньої відмови від договору сурогатного материнства батьками-замовниками. Дослідження проведено в контексті порівняльного аналізу відмови від цивільно-правових договорів загалом та договорів сурогатного материнства зокрема. Вивчено питання юридичної можливості таких дій та їх правові наслідки. Paper is devoted to a detailed study of the Institute of unilateral rejection of surrogacy contract father’s customers. Research conducted in the context of comparative analysis of non-civil contracts in general and in particular surrogacy contracts. Analyzes the legal possibility of such actions and their legal consequences. After all obligations of genetic parents to take the child born by a surrogate mother is not defined in law. The denial genetic parents of the child is placed in the scope of an «abandonment of the contract», for which responsibility is not provided. Therefore, the development of possible reasons for the refusal of the contract is the key to solving the problem of violation of contractual terms and conditions of surrogacy and the establishment of mechanisms for the protection of children born with the help of this program.
Unilateral Termination of the Contract of Surrogacy
Keywords: сурогатне материнство; сурогатна мати; договір сурогатного материнства; surrogacy; surrogate mother; surrogate motherhood contract